Yoruba Indigenous Music as Alternative Tool for Child Education - Sunday Olufemi Akande (Yoruba Studies Review, 2024)
Since music is a component of culture, it is essential to education. The importance of Yoruba traditional music in their education cannot be overstated, since the goal of education is to develop a child who is capable of being a productive member of society and who complies with social norms and customs. Given that traditional beliefs, rituals, norms, and social structures are often the foundation of musical notions and practices, the effects of Yoruba music on children become increasingly plausible. This cultural phenomenon research is necessary because of the connections between music, culture, and education. This study looks at how a Yoruba child's education was impacted by the shape, lyrics, and performing techniques of indigenous music. It will also provide a fitting explanation of the background of Yoruba music. A few chosen pieces of indigenous music were examined to establish the use of indigenous music as alternative tool historical, arithmetic, moral and health education. This study concludes that the inherent worth of indigenous music is a useful and alternative tool for teaching Yoruba children, especially in early childhood education. The study suggests that Yoruba people should value the singing of Indigenous music in their homes, community and that indigenous music should be incorporated into the curriculum and taught in elementary, secondary, and higher institutions.